2014
DOI: 10.1007/s00330-014-3540-z
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral computed tomography angiography using a 70 kVp protocol: improved vascular enhancement with a reduced volume of contrast medium and radiation dose

Abstract: • Cerebral CT angiography at 70-kVp substantially improved vascular enhancement • Subjective image quality was better at 70-kVp, with lower radiation dose • The volume of contrast media can be substantially reduced at 70-kVp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 25 publications
3
10
0
Order By: Relevance
“…Similar changes in dose for the same CNR (horizontal displacements in Fig. 4) are reported in recent clinical and phantombased studies 10,11 for the CT angiography protocol. Clinical CTP using the same mAs for reduced kVp, 13 is represented in Figure 4 as the diagonal shifts between kVp curves to reduced dose and CNR.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Similar changes in dose for the same CNR (horizontal displacements in Fig. 4) are reported in recent clinical and phantombased studies 10,11 for the CT angiography protocol. Clinical CTP using the same mAs for reduced kVp, 13 is represented in Figure 4 as the diagonal shifts between kVp curves to reduced dose and CNR.…”
Section: Discussionsupporting
confidence: 84%
“…Recent clinical studies have examined the influence on image quality and radiation dose offered by 70 kVp over higher energy spectra. Qualitative measures of image quality for brain angiography 10,11 for 70 kVp over 120 kVp, found increased noise, increased CT numbers expressed in Housfield Units (HU), with similar image quality and significant dose saving (85% less). Comparison between 80 kVp with iterative reconstruction against 70 kVp with filtered backprojection (FBP) and different mAs for CTP achieved similar image quality at less dose and no significant differences in parametric maps.…”
Section: Introductionmentioning
confidence: 99%
“…for CTA, 6,11,18,21 chest CT, 22 paediatric CT 23 and cranial CT. 24 These studies also showed feasibility, diagnostic image quality and a potential for reduction of radiation dose and CM. Up to date, only two studies have reported the results for dual-source 70-kVp CTPA.…”
Section: Imaging Characteristicsmentioning
confidence: 85%
“…On the axial images, the vascular attenuation (in Hounsfield units) of the internal carotid artery at the level of distal bifurcation and the image noise were measured by a board-certified radiologist (E-SC) with the same method as in the previous study 10. The contrast-to-noise ratio (CNR) was then calculated using the following formula:11 CNR=(mean arterial attenuation value−mean brain parenchyma attenuation value)/image noise.…”
Section: Methodsmentioning
confidence: 99%